MEDIA E-BOOKLET POLA MAKAN GIZI SEIMBANG TERHADAP PENGETAHUAN REMAJA SEBAGAI UPAYA PENCEGAHAN DIABETES TIPE 2 - Fairuz, Alya; Herdhianta, Dhimas (Jurnal Kesehatan Siliwangi, 2024)
Non-Communicable Diseases Indonesia a health problem and cause of death. Diabetes is health problem continues to increase cases every year. In 2022, diabetes in West Java was 644,704 people, in Bandung 2022 there were 45,465 people. According Riskesdas 2018, the age of >15 years has increased to 10.9% and 49.6% of adolescents don’t implement healthy nutritious diet. The largest constumer fast food is teenagers recorded at 69%. Factors can effect risk type 2 diabetes are due to lack of knowledge a balanced nutrition. E-booklet to be effective in increasing knowledge about balanced nutrition in adolescents. Develop media on adolescent knowledge effort to prevent type 2 diabetes with 4D approach. The research use R&D with a 4D media development model (Define, Design, Develop, Dissemination). The research was conducted at Mekar Arum School, with sample of 88. The define stage produces media need according to characteristics the target, the design stage contains media design matrix, the development stage carried out material, media tests, small-scale tests with very feasible results, and statistical tests produce an average adolescent knowledge score before being given e-booklet media by 66.8. The average knowledge score after being given e-booklet media was 86.4. The percentage increase knowledge adolescents was 29%. The p value of adolescents knowledge before and after being given e-booklet media was (p=0.000). The media made in category of very suitable for use and significant increase in knowledge after being educated on the balanced nutrition diet e-booklet media as effort to prevent type 2 diabetes.